L-Cysteine Alleviates Myenteric Neuron Injury Induced by Intestinal Ischemia/Reperfusion via Inhibitin the Macrophage NLRP3-IL-1β Pathway - Yifei Gao; Haojie Zhang; Yujin Wang; Ting Han; Jing Jin; Jingxin Li; Yan Tang; Chuanyong Liu; Chuanyong Liu (Frontiers Media S.A., 2022)
Ischemia/reperfusion injury is a common pathophysiological process in the clinic. It causes various injuries, multiple organ dysfunction, and even death. There are several possible mechanisms about ischemia/reperfusion injury, but the influence on intestinal myenteric neurons and the underlying mechanism are still unclear. C57BL6/J mice were used to establish the ischemia/reperfusion model in vivo. Peritoneal macrophages were used for ATP depletion and hypoxia/reoxygenation experiment in vitro. L-cysteine, as the substrate of hydrogen sulfide, is involved in many physiological and pathological processes, including inflammation, metabolism, neuroprotection, and vasodilation. In the current study, we confirmed that intestinal ischemia/reperfusion led to the injury of myenteric neurons. From experiments in vitro and in vivo, we demonstrated that L-cysteine protected myenteric neurons from the injury. AOAA reversed the protective effect of L-cysteine. Also, L-cysteine played a protective role mainly by acting on intestinal macrophages via decreasing the expression of NLRP3, cleaved caspase-1, and mature IL-1β. L-cysteine increased cystathionine beta synthase and H2S produced by intestinal macrophages to protect myenteric mature neurons and enteric neural precursor cells from apoptosis. Moreover, the addition of IL-1β-neutralizing antibody alleviated the injury of myenteric neurons and enteric neural precursor cells caused by intestinal ischemia/reperfusion. Our study provided a new target for the protection of myenteric neurons in clinical intestinal ischemia/reperfusion injury.